The Differences in Coping with Stress Between Male and Female High School Students in Mathematics Learning - Nabila, Aliffia Salfa; Handayani, Isnaini (Unnes Journal of Mathematics Education, 2024)
The phenomenon of students experiencing stress in learning mathematics is commonplace in this era of globalization. It is not uncommon for students to feel afraid when facing material or assignments presented by teachers at school. Therefore, this research aims to identify stress-coping strategies used by high school students in dealing with mathematics learning based on gender. This research uses descriptive quantitative methods. Data was obtained through a questionnaire containing 46 statement items, then distributed via Google Forms and statement sheets to students. The research respondents consisted of 89 students from tenth graders in one of the high schools in Tambun Selatan, Bekasi, West Java. Data analysis was carried out using the stress-coping percentage method. The research results show that both male and female students tend to use emotion-centered coping strategies, with a percentage of male respondents was 57% and female respondents had a percentage of 79%. Also, the coping strategy section that focuses on emotions tends more towards the sub-indicator of accepting responsibility with a percentage of 76% for male students and 78% for female students. It can be said that there is no difference between male and female students in solving a problem.